Профилирующая практика (13.03.02) электронный курс - Бейерлейн Е. В. Евгений Викторович; Гречушников В. В. Владислав Викторович; Дмитриенко В. Н. Виталий Николаевич; Образцов К. В. Константин Валентинович; Попов М. М. Михаил Михайлович; Муравлев А. И. Алексей Игоревич; Тютева П. В. Полина Васильевна; Шестакова В. В. Вера Васильевна; Шолохова И. И. Ирина Игоревна (Томск, TPU Moodle, 2022)
Заглавие с экрана